Deciphering the effects of hexagonal and monoclinic structure distribution on the properties of Li-rich layered oxides. Issue 28 (10th March 2021) - Ren, Qingqing; Xie, Huixian; Wang, Minjun; Ding, Xiaokai; Cui, Jiaxiang; Luo, Dong; Liu, Chenyu; Lin, Zhan
Abstract : Uniform distribution of Li2 MnO3 and LiMO2 structures in a Co-free Li-rich layered oxide contributes to excellent electrochemical performance and storage stability. Abstract : Uniform distribution of Li2 MnO3 and LiMO2 components in a Co-free Li-rich layered oxide is achieved by treating precursors with NH3 ·H2 O, which expands the lattice parameter and promotes the activation of Li2 MnO3, resulting in excellent electrochemical performance. What's more, it also contributes to the storage stability of Li-rich layered oxides.